Mult 1st eq by 3; x-2y+3z = 0
Mult 2nd eq by 4: 2x - 3y + 4z = 1
Add 2nd and 3rd: -4y+5z = 2
Mut 1st by 2: 2x-4y + 6z = 0
Add that answer and 3rd eq: -5y + 7z = 1
5(-4y + 5z = 2) + -4(-5y + 7z = 1)
-20y + 25z = 10 + 20y - 28z = -4
z = -2
Sub into the 1st eq: x - 2y -6 =0
Sub into the 3rd eq: -2x-y-2 = 1
2(x-2y = 6) + (-2x-y=3)
2x - 4y = 12 + -2x -y = 3
y = -3
sub into the 3rd eq
-2x -(-3) +(-2) = 1
-2x +1 = 1
x = 0
It might be easier if you
a) multiplied the first equation by 3
b) the second equation by 4
algebra 1 - what are some methods of solving systems of linear equations
Algebra - Solving Linear Equations - Elimination Write whether each of these ...
algebra - Can anyone help me to understand algebra? Right now I am working on ...
algebra - I'm working on solving linear systems by substitution, here are the ...
Algebra 1A - How many solution sets do systems of linear inequalities have? Do ...
Algebra 1 - How many solution sets do systems of linear inequalities have? Do ...
Algebra - Solving systems of linear equations in 3 variables... 1) 3x-2y+2z=1 2...
Algebra - What similarities and differences are there between functions and ...
algebra - What are the similarities and differences between functions and linear...
algebra - I do not know how to solve the following systems of linear equations ...